Kimlik Krizi ve Kişilik Bozuklukları: Otantikliğin Aracı Rolü - Taşçı, Faik; Bilge, Yusuf; Bilge, Yusuf; Taşcı, Ahmet Fatih; Taşçı, Faik (Kıbrıs Ruh Sağlığı Enstitüsü, 2023)
Bu çalışmanın amacı Erikson’un Psikososyal Kişilik Kuramına göre hayat boyu devam eden kimlik inşasının kişilik bozuklukları ile olan ilişkisinde kişinin kendi kimliğine uygun hareket edebilme kapasitesi olarak tarif edilebilecek otantikliğin aracı rolünü incelemektir. Yaş aralığı 18-79 (Ort.= 34.83, SS. = 11.71) olan 230’u kadın (%53.6) ve 199’u erkek (%46.4) olmak üzere toplam 429 kişinin katıldığı çalışma, kesitsel bir tarama çalışmasıdır. Analiz sonuçlarına göre tüm değişkenler birbirleriyle anlamlı ve güçlü ilişkiler gösterirken bağlılık temel gücü ile kişilik bozukluğu kümeleri arasındaki ilişkide otantikliğin kısmi aracı etkisi olduğu bulunmuştur. Bulgular, Erikson’un yaşam boyu devam eden kimlik ve kişilik gelişimi iddiası ile varoluşçu yaklaşımdaki dinamik otantiklik anlayışının birbirini tamamlar nitelikte olduklarını ve bunların sağlıklı bir şekilde gerçekleşmemesi durumunda ise patolojinin ortaya çıktığını göstermektedir.

The main purpose of this study is to examine the mediating role of authenticity, which can be defined as the capacity to act in accordance with one's own identity, in the relationship between personality disorders and identity construction, which continues throughout life, according to Erikson's psychosocial personality theory. Participating in a total of 429 individuals [230 females (53.6%) and 199 males (46.4%), aged between 18 and 79 (M.= 34.83, SD.= 11.71)], the study was a cross-sectional screening study. According to the results of the analysis, while all the variables showed significant and strong relationships with each other, it was found that authenticity had a partial mediating effect on the relationship between the core strength of commitment and personality disorder clusters. The results of the research have shown that Erikson's lifelong claim of identity and personality development and dynamic authenticity in the existential approach are complementary to each other, and if these do not occur in a healthy way, pathology emerges.
Identity Crises and Personality Disorders: Mediator Role of Authenticity
This study is produced from the master's thesis titled "Investigation of Personality Disorders in DSM-5 in terms of Psychosocial Developmental Periods and Existential Authenticity"
Keywords: Kimlik; Kimlik krizi; Otantiklik; Kişilik bozuklukları; İdentity; İdentity crisis; Authenticity; Personality disorders